2009
DOI: 10.1103/physrevlett.102.027602
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric-Paraelectric Transition inBiFeO3: Crystal Structure of the OrthorhombicβPhase

Abstract: A detailed investigation using variable temperature powder neutron diffraction demonstrates that BiFeO 3 undergoes a phase transition from the ferroelectric α phase

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
190
4
12

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 310 publications
(231 citation statements)
references
References 24 publications
25
190
4
12
Order By: Relevance
“…The critical distances from the ion centers O, Bi and Fe to the bond line The sign and strength of magnetic couplings in BiFeO 3 was calculated in the temperature range from 25º up to 945º С. We took the crystallographic parameters and atom coordinates in γ-BiFeO 3 [18,32], β-BiFeO 3 [19], α-BiFeO 3 [21] and Bi 0.93 La 0.07 FeO 3 [24], as well as the ionic radii of Fe 3+ , Bi 3+ and O 2-( = 0.645 Ǻ, = 1.17 Ǻ (for γ-and β-BiFeO 3 ), = 1.103 Ǻ (for α-BiFeO 3 ), = 1.40 Ǻ) determined in [59], as initial data for calculations. The method high sensitivity to any slight change of atom coordinates comprises simultaneously its advantage and disadvantage.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The critical distances from the ion centers O, Bi and Fe to the bond line The sign and strength of magnetic couplings in BiFeO 3 was calculated in the temperature range from 25º up to 945º С. We took the crystallographic parameters and atom coordinates in γ-BiFeO 3 [18,32], β-BiFeO 3 [19], α-BiFeO 3 [21] and Bi 0.93 La 0.07 FeO 3 [24], as well as the ionic radii of Fe 3+ , Bi 3+ and O 2-( = 0.645 Ǻ, = 1.17 Ǻ (for γ-and β-BiFeO 3 ), = 1.103 Ǻ (for α-BiFeO 3 ), = 1.40 Ǻ) determined in [59], as initial data for calculations. The method high sensitivity to any slight change of atom coordinates comprises simultaneously its advantage and disadvantage.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the relation of the above phenomena, we calculated the sign and strength of magnetic couplings in BiFeO 3 on the basis of the structural data [18,19,21,24, 32] at temperatures from 25º up to 945º С (Table 3, Fig. 4).…”
Section: Relation Of the Transition Magnetic Order-magnetic Disorder mentioning
confidence: 99%
See 2 more Smart Citations
“…The first objective is to test the recent space group determination of the γ-phase reported by Arnold et al [1] as being orthorhombic. Their definitive neutron study showed that the γ-phase is indeed stable (which in itself had been controversial), and that it has the same orthorhombic Pbnm orthoferrite symmetry as does the β-phase.…”
Section: Introductionmentioning
confidence: 99%